PENINGKATAN LAJU PERTUMBUHAN AWAL STEK BATANG TANAMAN ANGGUR DENGAN LIMBAH URINE SAPI - Pratiwi, Yeni Ika; Nisak, Fauziatun; Gunawan, Bambang (JHP17 (Jurnal Hasil Penelitian), 2019)
Cattle are a type of ruminants which are relatively more favored by the general public; but this increase in livestock business has a positive impact, namely producing main products such as meat, milk, and also has a negative impact in the form of livestock waste, which is residual waste in the form of solid and liquid waste such as feces, urine and feed residue. The application of appropriate technology by utilizing cow urine liquid waste into fertilizing material or fertilizer after going through a fermentation process to become a liquid organic fertilizer that is beneficial to plants. This study aims to determine the effect of giving urine urine POC concentration and soaking time and its interaction on stem cuttings of vines so as to increase the initial growth rate. Based on the results of the study, it can be concluded as follows: 1. There is a significant interaction effect of cow urine POC concentration factors and soaking time on the length of shoots of grape cuttings, the best value achieved by the P3L2 treatment combination gives a better value of 16.17 cm at the end observation (42 days) compared to other treatment combinations. 2. There is a significant effect of cow urine POC concentration factors as well as immersion long factors on the growth of grape cuttings on the variables studied, including: speed of engagement, number of leaves; although it has no significant effect on the variable bud diameter, number of shoots, root length and number of root cuttings. Overall the best value tends to be achieved by the treatment of P3 and P4, namely 30-40 ml per liter of water and L2 treatment, which is 30 minutes soaking time.Keywords: Cattle Urine POC, Vine Stem Cuttings.